ҚAТЛАМЛИ ТУПРОҚЛAРДA ЕР УСТИ ВA СИЗОТ СУВЛAРИ ЎЗAРО БОҒЛAНГAН ОҚИМИНИНГ ГИДРОДИНAМИК МОДЕЛИ - Авлакулов, Мейли; Қодиров, Исомиддин (Innovatsion texnologiyalar, 2022)
The article deals with the modeling of the process of saturated-unsaturated filtration in layered soils using a two-dimensional hydraulic model in the aeration and saturation zone. At the same time, for modeling mass transfer by interacting currents of surface and ground waters and taking into account moisture migration in the humidification zone, planned hydraulic models of the interconnected flow of ground and surface waters can be effectively used.